PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PEREDARAN NARKOTIKA DI KAMPUNG DALAM KECAMATAN SENAPELAN KOTA PEKANBARU - Devi Angriyani; Erdianto Effendi; Syaifullah Yophi Ardiyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
In general, narcotics can be said as substances or drugs, both natural,synthetic, and semi-synthetic which cause a decrease in consciousness,hallucinations, and arousal. The special sanctions in the Narcotics Law are anumber of criminal sanctions for those who become intermediaries in buying andselling transactions can immediately be said to be intermediaries in the NarcoticsCirculation. Research on narcotics abuse at the Senapelan District Police,Kampung Dalam Pekanbaru City aims to find out law enforcement againstnarcotics trafficking crimes, obstacles and efforts in dealing with narcotics abuse.This type of research can be classified in the type of sociological research,because in this study the author directly conducts research at the location orplace under study in order to provide a complete and clear picture of the problembeing studied. This research was conducted at the Resort Police of SenapelanDistrict, Pekanbaru City, while the population and sample are all parties relatedto the problems studied in this study, the data sources used, primary data, andsecondary data, and tertiary data, data collection techniques in this study byobservation and interviews.From the results of the study as follows: law enforcement againstnarcotics abuse in Kampung Dalam Kota Pekanbaru based on investigations andraids that have been carried out for places in Kampung Dalam that have beenproven to have committed violations, especially in the distribution of Narcotics,the place is sealed and strict action is taken in accordance with the provisionsregulations, and obstacles in law enforcement against Narcotics Abuse inKampung Dalam Pekanbaru City are the lack of supervision from the governmentto monitor activities carried out by the people of Senapelan Subdistrict, KampungDalam, so that there are still many places that are not supervised, lack ofawareness and community participation so that the police as if working alonerevealed the use of Narcotics, and the lack of personnel in an effort to curbviolations.Keywords: Narcotics, Police, Narcotics Abuse, Investigation, Investigation.